2020
DOI: 10.1016/j.acuroe.2020.10.006
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 outbreak on urolithiasis emergency department admissions, hospitalizations and clinical management in central Italy: a multicentric analysis

Abstract: Introduction and objectives We aimed to evaluate how the corona virus disease of 2019 (COVID-19) outbreak influenced emergency department (ED) admissions for urolithiasis, hospitalizations and clinical management of the hospitalized Patients. Patients and methods We conducted a multicentric retrospective analysis of ED admissions in three high volume urology departments (one directly involved in COVID-19 patients management and two not involved) in Rome - Italy between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 13 publications
0
22
1
2
Order By: Relevance
“…A report 3 from three medical centres in the state of New York found an increase in paediatric perforated appendicitis compared with uncomplicated appendicitis during the surge of COVID-19 outbreak. Similarly, a number of reports have documented decreases in emergency visits for kidney stone disease, with an increase in severe presentations necessitating admission 14 , 15 . These data are consistent with the findings of the present study, where there was a moderate increase (0.7 per cent) in the category urolithiasis (N20–N23).…”
Section: Discussionmentioning
confidence: 94%
“…A report 3 from three medical centres in the state of New York found an increase in paediatric perforated appendicitis compared with uncomplicated appendicitis during the surge of COVID-19 outbreak. Similarly, a number of reports have documented decreases in emergency visits for kidney stone disease, with an increase in severe presentations necessitating admission 14 , 15 . These data are consistent with the findings of the present study, where there was a moderate increase (0.7 per cent) in the category urolithiasis (N20–N23).…”
Section: Discussionmentioning
confidence: 94%
“…The comparison of admission numbers only with data from 2019 harbors the possibility that the observed effects are caused by year‐dependent fluctuations in admission numbers. However, a comparison with previous year's data have also been considered a valid method of comparison in several other studies investigating changes in health care utilization during the COVID‐19 pandemic 1‐3,8‐11,13‐15,27,42‐45 …”
Section: Limitationsmentioning
confidence: 99%
“…Conversely, in the reopening phase, the admission rate and clinical presentations were similar to those in the same period in 2019, and the expected overload of complicated cases in the months following the lockdown was not demonstrated. 8 That said, we can assume that the COVID-19 lockdown led to an increasing rate of complicated ureteral stone disease that required more interventional procedures compared to the corresponding period in 2019. Our findings are in line with the study by Gul et al, which also demonstrated that serum creatinine levels, white blood cell counts, and number of interventional procedures were significantly higher in the COVID-19 lockdown period.…”
Section: Discussionmentioning
confidence: 99%
“…7 During the COVID-19 lockdown, there was a reduction in ED admissions for urolithiasis, associated with increased complication rates and worse clinical presentation, which led to the anticipation of a possible overload of complicated cases in the following months. 8 The reopening phase after the lockdown in Italy started gradually in May 2020. To date, no studies have evaluated the trend in ED admissions, clinical presentation, hospitalization, and treatment for upper tract stone disease during the reopening phase.…”
Section: Introductionmentioning
confidence: 99%